2015
DOI: 10.1093/jxb/erv454
|View full text |Cite
|
Sign up to set email alerts
|

Dormancy-associated MADS-box genes and microRNAs jointly control dormancy transition in pear (Pyrus pyrifoliawhite pear group) flower bud

Abstract: HighlightShort-term chilling in autumn activates the accumulation of CBF, which directly promotes DAM expression. DAMs subsequently inhibit FT2 expression to induce endo-dormancy; miR6390 might degrade DAM genes to release endo-dormancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
189
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(209 citation statements)
references
References 87 publications
(145 reference statements)
10
189
0
Order By: Relevance
“…The remaining DAM -like and SVP -like coding sequences were amplified using oligonucleotide primers designed from ‘Royal Gala’ partial sequences and previously reported apple DAM / SVP / JOINTLESS genes (Supplementary Table S1). The predicted full length amino acid sequences were aligned with the full length of amino acid sequences of Arabidopsis SVP (AT2G22450) and AGL24 (AT4G24540), potato StMADS11 (AF008652), apple MdDAM1 (KT582786), MdDAM2 (KT582787), MdDAM4 (KT582789), MdJb (LC004730), apricot PmDAM6 (AB437345), leafy spurge EeDAM2 (EU339320), three pear DAM ( PpyDAM1 , PpyDAM2 and PpyDAM3 ) and one pear SVP ( PpySVP) (Niu et al, 2016), six peach DAM ( PpeDAM1, PpeDAM2, PpeDAM3, PpeDAM4, PpeDAM5 and PpeDAM6) (Bielenberg et al, 2006) and one peach SVP ( PpeMADS57 ) (Wells et al, 2015), trifoliate orange PtSVP (FJ373211), kiwifruit SVP gene s ( AcSVP1 , AcSVP2, AcSVP3 and AcSVP4 ) (Wu et al, 2012). The alignments were performed using Clustal W (opening = 10, extension = 0.2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining DAM -like and SVP -like coding sequences were amplified using oligonucleotide primers designed from ‘Royal Gala’ partial sequences and previously reported apple DAM / SVP / JOINTLESS genes (Supplementary Table S1). The predicted full length amino acid sequences were aligned with the full length of amino acid sequences of Arabidopsis SVP (AT2G22450) and AGL24 (AT4G24540), potato StMADS11 (AF008652), apple MdDAM1 (KT582786), MdDAM2 (KT582787), MdDAM4 (KT582789), MdJb (LC004730), apricot PmDAM6 (AB437345), leafy spurge EeDAM2 (EU339320), three pear DAM ( PpyDAM1 , PpyDAM2 and PpyDAM3 ) and one pear SVP ( PpySVP) (Niu et al, 2016), six peach DAM ( PpeDAM1, PpeDAM2, PpeDAM3, PpeDAM4, PpeDAM5 and PpeDAM6) (Bielenberg et al, 2006) and one peach SVP ( PpeMADS57 ) (Wells et al, 2015), trifoliate orange PtSVP (FJ373211), kiwifruit SVP gene s ( AcSVP1 , AcSVP2, AcSVP3 and AcSVP4 ) (Wu et al, 2012). The alignments were performed using Clustal W (opening = 10, extension = 0.2).…”
Section: Methodsmentioning
confidence: 99%
“…In Rosaceae, DAM genes form a subclade separate from true Arabidopsis SVP -like and potato StMADS11 -like subclades (Velasco et al, 2010; Wells et al, 2015; Niu et al, 2016; Porto et al, 2016). In peach, the SVP gene family is expanded to six DAM genes, tandemly arranged on peach chromosome 1 (Jimenez et al, 2009; Illa et al, 2011), one true SVP ortholog PpeMADS57 and the less similar PpeMADS58 , located on chromosomes 6 and 8, respectively (Wells et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…OsMIR444 participates in a miRNA/MADS/TCP/D14 (miMTD) regulation module, in which D14 functions in strigolactone (SL) signaling to control tillering, by suppressing OsMADS57 expression (Guo et al, 2013). In pear trees, miR6390 is involved in the transition from endormancy to ecodormancy by targeting PpDAM transcripts, degrading them and stimulating the release of PpFT2 (Niu et al, 2015). Overexpression of the MbDRB1 , a gene involved in miRNA biogenesis in Malus baccata , increased the level of adventitious rooting, curly leaf, and columnar-like architecture (You et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These include the DORMANCY ASSOCIATED MADS BOX (DAM) genes, which share a high percentage of homology with SHORT VEGETATIVE PHASE (SVP) and AGAMOUS-LIKE24 (AGL24) of Arabidopsis thaliana. DAM genes were identified in Euphorbia esula (leafy spurge), Malus domestica (apple), Pyrus pyrifolia (Asian pear), Prunus persica (peach) and Actinidia chinensis (kiwifruit; Horvath et al, 2010;Wu et al, 2011;Mimida et al, 2015;Niu et al, 2016). Detailed expression studies revealed that their activity correlates perfectly with the dormancy state of the vegetative buds, with high expression during the low temperature period which decreases prior to dormancy release or bud burst (Leida et al, 2012).…”
Section: Diversification Of Pebp Functions In Bulbous and Other Plantmentioning
confidence: 99%